Books & bewitchment - Jewell, Isla (Arcadia Falls, 2026)
"Dutiful and hard-working, Rhea Wolfe lives a simple, if mundane, life with her pet parrot in small-town Alabama. Sure, she may not love her desk job working for an insurance agency. And her on-again-off-again relationship with the local mechanic may not have the fiery passion she's read about in her favorite books. Still, things are stable, which is more than she can say about the two hopelessly immature younger sisters who rely on her. But when Rhea's estranged grandmother dies, leaving her everything-including a magical heritage Rhea never knew she carried-she finds herself in Arcadia Falls, the quaint mountain town her mother made her swear to avoid at all costs. While the defunct video store she's also inherited needs a serious upgrade, Rhea's lucky that resident handyman Hunter Blakely is more than happy to help-and more than easy on the eyes. If only he wasn't the grandson of her grandmother's sworn enemy in witchcraft. As Rhea works to build a future, strange occurrences begin to make her think someone-or something-is trying to drive her out. As she gets ever closer solving the mystery, each clue she uncovers points to Arcadia Falls' magic hanging in the balance. To keep her new home safe, Rhea must step into her enchanted birthright . . . before it's too late"-- Provided by publisher.